Аdministrative and legal status of public associations of persons with disabilities as participants in public relations in the field of protection of their rights - Zhuravlyova, Zoria (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
In the article the author draws attention to the importance of social formations in the process of introduction of a democratic developed civil society. The author emphasizes that the right to association of citizens, including persons with disabilities, is one of the basic (basic) civil rights and is recognized by international law as an integral element of the legal personality of man and citizen. Emphasis is placed on the fact that public associations, which are established and operate to protect the rights and legitimate interests of persons with disabilities, providing them with equal opportunities with other citizens, are a form of their social protection. It is determined that the effectiveness of the implementation of civil legal personality of these associations depends on the legal status to which such associations are endowed with current norms. It is emphasized that in order to realize the interests of persons with disabilities defined by law, such public associations should be endowed with the appropriate status, which ensures the consolidation of their powers and provides an opportunity to realize the purpose of their creation. The concept of administrative and legal status of public associations of persons with disabilities as participants in public relations in the field of protection of their rights is formed and their character traits are highlighted. The article emphasizes that the administrative and legal status of public associations is characterized as a set of rights and responsibilities that are realized in the administrative legal relations that arise between public associations and state bodies, local governments. The author highlights the characteristics of a public association of persons with disabilities, namely the creation, existence and functioning separately from the state; formation on a voluntary basis; non-profit activity; self-organization and self-government.